PERAN ORANG TUA DALAM MEMOTIVASI BELAJAR ANAK USIA DINI DI DESA SUNAN AMPEL KELURAHAN AMPELDENTO KECAMATAN PAKIS KABUPATEN MALANG - Reni Indra Wahyuni; Ika Ratih Sulistiani; Mutiara Sari Dewi (UNISMA, 2020)
Based on Law No 20 Th 2003 article 1 paragraph 1 about education is a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have the spiritual power of diversity, self-control, personality, noble moral intelligence, and skills that are it needs itself, society, nation and state. The role of parents is very important in providing comfort, warmth and security for their children. Present beside the child accompanying him to study, read books, even play it can make children feel cared for. Because parents namely father and mother is a very valuable facility and is second to none. The role of parents is very big in fostering, educating, motivating, and raising children to succeed and achieve all their ideals. Whatever obstacles parents face must be able to be overcome properly so that children's learning activities remain smooth and can achieve better performance. The solution is to provide habituation in the home so that children can be disciplined and easily carry out a learning activity.